PENERAPAN METODE HOLT WINTERS UNTUK PERAMALAN HARGA SAHAM PT PRODIA WIDYAHUSADA TBK - Prasetyo, Muhammad Ary; Mahdiyah, Umi; Swanjaya, Daniel (Universitas Budi Luhur, 2023)
The increase in the growth of Indonesian investors is partly due to the Covid-19 pandemic. Investors are moving their assets to investment instruments. One of them is stocks. The research aims to do stock forecasting or prediction to make it easier for investors to determine their investment decisions. Forecasting is an activity to calculate future conditions by utilizing past data and data that affect the situation to be predicted. This research uses forecasting methods with two Holt Winters methods, namely the Additive method and the Multiplicative method with PT Prodia Widyahusada TBK stock price data. To determine the feasibility of the forecasting model, this study uses MAPE to determine the error rate of the method in forecasting. The results of forecasting using the Holt Winters Additive and Holt Winters Multiplicative methods get MAPE values that are both very good. The MAPE value in stock forecast use Holt Winters Additive model method gets a value of 1.81% while the MAPE value in stock forecasting using the Holt Winters Multiplicative method gets a value of 2.06%. From the results of the research that has been done, it can be concluded that the MAPE value in stock forecasting using the Holt Winters Additive model method has the smallest error rate